Single-Stage Breast Reconstruction Using an All-In-One Adjustable Expander/Implant. Issue 1 (January 2018) - Azzi, Alain J.; Zammit, Dino; Lessard, Lucie
Abstract : Background: When tissue expansion is necessary in breast reconstruction, a single-stage approach is possible using adjustable expander/implants, with or without the use of acellular dermal matrix. We aimed to present the senior author's single-stage experience over a period of 12 years using combined expander/implants in breast reconstruction. Methods: This is a Single-institution, retrospective review of breast reconstruction with combined expander/implants from 2002 to 2014. Logistic regression was performed to evaluate the impact of multiple variables on long-term outcomes. Results: A total of 162 implants in 105 patients were included in this study. Mean follow-up time was 81.7 months (SD, ± 39.2; range, 15–151). Complication rates were as follows: 0.62% extrusion, 1.2% mastectomy flap necrosis, 1.2% hematoma, 1.9% dehiscence, 2.5% seroma, 4.9% infection, and 15.4% deflation. The following associations were identified by logistic regression: adjuvant radiotherapy and capsular contracture ( P = 0.034), tumor size and deflation ( P = 0014), and smoking history and infection ( P = 0.013). Conclusions: Overall, 81% of breasts were successfully reconstructed in a single stage. Single-stage reconstruction using all-in-one expander/implants reduces costs by eliminating the need for a second procedure under general anesthesia and can achieve results comparable with other alloplastic reconstructions reported in the literature. Abstract : Supplemental Digital Content is available in the text.